The masked water snakes of the genus Homalopsis Kuhl & van Hasselt, 1822 (Squamata, Serpentes, Homalopsidae), with the description of a new species - Murphy, John C.; Voris, Harold K.; Murthy, B. H.c.k.; Traub, Joshua; Cumberbatch, Christina (Zootaxa, 2012)
Masked water snakes of the genus Homalopsis are abundant in the wetlands of Southeastern Asia. Currently, two speciesare recognized, the widespread H. buccata Linnaeus and the Mekong drainage endemic H. nigroventralis Deuve. On thebasis of morphology we resurrect H. hardwickii Gray and H. semizonata Blyth and describe a new species from Indochina.We establish a neotype for Coluber buccatus Linnaeus and examine the status of other names associated with this species.Homalopsis species can be distinguished from each other on the basis of dorsal scale row counts, the scales in the ocularring, and other head scale architecture. The new species, Homalopsis mereljcoxi, is distinguished from all others by itsone postocular and one postsubocular scale, and a higher dorsal scale row count (40–47 scale rows at midbody) that arereduced to more than 30 scale rows at the body’s posterior. The new species is heavily exploited for the skin trade at TonleSap, Cambodia. Homalopsis likely contains other cryptic species that have evolved in the changing aquatic habitats of Southeast Asia. A key to the species of Homalopsis is provided.